Ethnomedicinal Applications of Fish Species Among Local Communities of Medir Haor, Bangladesh (Research in Agriculture Livestock and Fisheries, 2025)
Fish play a vital role in food security and cultural identity in Bangladesh; however, their use in traditional medicine remains inadequately documented. This study aimed to document the ethnomedicinal uses of fish species in Medir Haor, a wetland ecosystem in northeastern Bangladesh, and to assess the status of intergenerational knowledge transmission. Conducted between January and June 2025, the study employed community consultations, informal discussions (adda), and semi-structured interviews with traditional knowledge holders and local students. A total of 11 distinct therapeutic applications involving 10 fish species were documented. These ranged from the use of the Indian mottled eel (Anguilla bengalensis) for the treatment of hemorrhoids to the use of the striped snakehead (Channa striata) for anxiety, the latter uniquely associated with local beliefs related to supernatural entities. Additionally, four fish species were identified as being deliberately avoided due to perceived preventive health concerns. Notably, a pronounced intergenerational knowledge gap was observed, with younger respondents largely unaware of these ethnomedicinal practices. The findings indicate that this localized traditional knowledge, although still practiced by a limited group, is critically endangered. Immediate documentation is therefore essential to preserve this intangible cultural heritage, which holds considerable potential for future ethnopharmacological research and biocultural conservation. Overall, the study underscores the urgency of safeguarding ethnomedicinal knowledge against erosion driven by modernization and environmental change.Res. Agric. Livest. Fish. Vol. 12, No. 3, December 2025: 547-554